2022
DOI: 10.3389/fbioe.2022.853436
|View full text |Cite
|
Sign up to set email alerts
|

Application of Amorphous Calcium Phosphate Agents in the Prevention and Treatment of Enamel Demineralization

Abstract: Enamel demineralization, as a type of frequently-occurring dental problem that affects both the health and aesthetics of patients, is a concern for both dental professionals and patients. The main chemical composition of the enamel, hydroxyapatite, is easy to be dissolved under acid attack, resulting in the occurrence of enamel demineralization. Among agents for the preventing or treatment of enamel demineralization, amorphous calcium phosphate (ACP) has gradually become a focus of research. Based on the noncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…The N-terminus is an important domain of amelogenin for assisting mineralization ( Dissanayake et al, 2020 ). Through its tyrosine enrichment segment (TRAP) on the N-terminus, amelogenin interacts with calcium and phosphorus ions, stabilizing them into an amorphous form ( Yan et al, 2022 ). There was no significant difference in remineralization between the peptide 1 and peptide 2 medium treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminus is an important domain of amelogenin for assisting mineralization ( Dissanayake et al, 2020 ). Through its tyrosine enrichment segment (TRAP) on the N-terminus, amelogenin interacts with calcium and phosphorus ions, stabilizing them into an amorphous form ( Yan et al, 2022 ). There was no significant difference in remineralization between the peptide 1 and peptide 2 medium treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…WSLs is one of the most common side effects of orthodontic treatment (Huang et al, 2022;Yan et al, 2022b). Recent study revealed that the incidence of WSLs reached 41.18%…”
Section: Discussionmentioning
confidence: 99%
“…584 Benefiting from this, some amorphous biominerals can be stabilized, opening up a range of applications. 327,585 Thrivikraman et al 548 adopted a supersaturated calcium and phosphate medium with a non-collagenous protein analog to direct the deposition of nanostructured apatite, both in the intra-and extrafibrillar spaces of collagen embedded with osteoprogenitor, vascular, and neural cells. This method could prepare bone-like tissue models with high levels of biomimicry, enabling nearly homogenous mineralization of human mesenchymal stem cells-laden collagen hydrogels with structural organization and elemental composition comparable to human bone (Fig.…”
Section: Chemical Self-assembly Strategiesmentioning
confidence: 99%
“…584 Benefiting from this, some amorphous biominerals can be stabilized, opening up a range of applications. 327,585…”
Section: Strategies For the Construction Of Bmt-inspired Synthetic Ma...mentioning
confidence: 99%